ANALISIS PEMAHAMAN KONSEP FISIKA SISWA PADA MATERI FLUIDA DAN PENERAPNNYA KELAS VIII MTsN KOTA PEKANBARU - Riska Apriliza; Azhar Azhar; Zulirfan Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to describe the level of understanding of students' physics concepts on fluid material and its application in the VIII class of MTsN Pekanbaru City. The population is all students the VIII class of MTsN in Pekanbaru City and the sample was taken using the Slovin formula with an error rate of 10%. The sample used by simple random sampling technique namely was 87students from MTsN 1 Pekanbaru and MTsN 3 Pekanbaru. The research instrument used questions test on the description of the fluid material and its application. Descriptive analysis was conducted to see the results of the students' physics concept understanding test using the criteria for understanding the physics concept of each indicator. Data collection techniques was in the form of scores on the results of understanding the concept of physics. The results showed that the average percentage of students' conceptual understanding in physics science subjects was in the medium category with a value of 47.05%. The category of conceptual understanding in the instrument consists of interpreting, exemplifying, classifying, summarizing, generalizing, comparing, and explaining.Key Words: Understanding Concept, Fluid and application